A cornucopia of bioactive compounds from leaves extract of Garcinia mangostana: a contrastive assessment of phytochemical constituents and their antioxidant activities influenced by organic solvents - Abd Samat, Nur Mardhiati Afifa; Abd Gani, Siti Salwa; Mansor, Hakiman; Ahmad, Khairulmazmi (Malaysian Institute of Chemistry, 2026)
The phytochemical richness of Garcinia mangostana has garnered increasing interest due to its potent therapeutic potential. This study presents a comprehensive evaluation of the effects of different organic solvents, ranging from non-polar to highly polar, on the extraction efficiency, phytochemical composition, and antioxidant activities of G. mangostana leaf extracts. Solvents, including hexane, toluene, chloroform, acetone, ethanol, methanol, and water, were employed to investigate the variation in extractive value, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities via DPPH and ABTS radical scavenging assays. Results revealed that polar solvents, particularly ethanol and methanol, yielded the highest levels of phenolics (4588.5 ± 58.1 and 4261.9 ± 55.7 mg GAE/g DW, respectively) and flavonoids (2352.22 ± 48.1 and 2870.37 ± 51.5 mg QE/g DW, respectively), which correlated strongly with their superior antioxidant activities. Despite its low phenolic content, hexane extract exhibited moderate ABTS activity, suggesting the presence of lipophilic antioxidants. Water showed the highest extractive value (79 ± 1.23%) but was less effective in recovering phenolic-rich fractions. This study highlights the critical role of solvent polarity in modulating the phytochemical and biofunctional profile of G. mangostana leaf extracts, providing a valuable framework for optimizing solvent selection in natural product research and functional formulation development.